On the record : music journalists on their lives, craft, and careers - Hilleary, Mike (University of Massachusetts Press, 2020)
"Rolling Stone, Creem, the Village Voice, SPIN, Billboard, Stereogum, Pitchfork. How did the music journalists who write for these popular publications break into the business? How have they honed their writing and interviewing techniques? How have they managed to thrive amid major changes in the industry, as print magazines have declined and digital publications have emerged? What does it take to turn a love of music into a professional writing career? Bringing together interviews from an impressive roster of over fifty music writers, Mike Hilleary offers up an engaging and wide-reaching examination of the past and potential future of music journalism. This accessible oral history contains professional insights into journalists' craft and purpose, practical advice, and essential life lessons from a diverse cast of music writers-ranging from long-respected veterans of the field such as Rob Sheffield, Jessica Hopper, Ann Powers, and Chuck Klosterman to must-read modern voices including Amanda Petrusich, Hanif Abdurraqib, Lindsay Zoladz, and Jayson Greene. Honest and absorbing, On the Record will educate and enlighten anyone who wants to write about music, or anyone who wants a better understanding about those who do"--